Durasi menyusu dan kejadian overweight pada remaja - Nurlaili Ramli; Madarina Julia; Toto Sudargo (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2012)
Background: Statistic showed an increasing number of overweight incidences among children in Aceh Province. However, relationship between breastfeeding and risk of overweight and obesity is still controversial due to strong confounding factors. Hence, the relationship between breastfeeding and obesity is unclear. To reduce the confounding factors, siblings analysis can be undertaken as children live in the same environment.Objective: To investigate the influence of siblings overweight status on breastfeeding duration and overweight incidence among adolescents and to explore other environmental and genetic factors related to overweight incidence in adolescents.Method: This was an observational-analytical study with a matched case control design. There were 50 subjects for each group. Subjects in the case group were taken from existing cases, while the control group was selected by purposive sampling by matching in age and gender. Paired t test, McNemar test and conditional logistic regression were performed to analyse the data.Results: Overweight adolescents have shorter breastfeeding duration than non-overweight adolescents. Multiple conditional logistic regression tests on overweight status in siblings showed that breastfeeding duration could reduce overweight incidence among adolescents (OR=0.81; 95%CI:0.69-0.96).Conclusion: Overweight adolescents have shorter duration of breastfeeding than those who were not overweight. Factors that affect the risk of overweight among adolescents in this study were mother’s education, adolescent’s eating behavior, mother’s overweight status and sibling’s overweight status.